2016
DOI: 10.21890/ijres.267371
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Secondary Mathematics Teachers’ Self-efficacy, Attitudes, and Use of Technology to Support Communication and Mathematics Literacy

Abstract: This article may be used for research, teaching, and private study purposes.Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.Authors alone are responsible for the contents of their articles. The journal owns the copyright of the articles.The publisher shall not be liable for any loss, actions, claims, proceedings, demand, or costs or damages whatsoever or howsoever caused arising directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
8
0
6
Order By: Relevance
“…Another research conducted by Letwinsky (2017) revealed a significant relationship between teachers' attitudes toward using technology for communication and personal selfefficacy, yet few reported using technology in this way. An important recommendation from Letwinsky (2017) study was to investigate why teachers who demonstrate key positive indicators for technology integration do not capitalize on the potential that communication technology provides to cultivate mathematics communication and literacy. Krammer (2006) has also examined the effectiveness of learning with classroom video.…”
Section: Resultsmentioning
confidence: 99%
“…Another research conducted by Letwinsky (2017) revealed a significant relationship between teachers' attitudes toward using technology for communication and personal selfefficacy, yet few reported using technology in this way. An important recommendation from Letwinsky (2017) study was to investigate why teachers who demonstrate key positive indicators for technology integration do not capitalize on the potential that communication technology provides to cultivate mathematics communication and literacy. Krammer (2006) has also examined the effectiveness of learning with classroom video.…”
Section: Resultsmentioning
confidence: 99%
“…Kemampuan siswa dalam mengkomunikasikan pemecahan masalah penting dikembangkan untuk menghadapi perkembangan zaman. Kemampuan siswa dalam berkomunikasi dan menyelesaikan masalah merupakan bagian dari keterampilan abad 21 (Letwinsky, 2017).…”
Section: Pendahuluanunclassified
“…El estudio de la autoeficacia docente se ha realizado en áreas específicas de conocimiento como, es el caso de Gil-Flores (2016) en profesores españoles de ciencias y Backhoff et al ( 2017), Lazarides et al (2018), Letwinsky (2017), Vizcaino et al (2015), en profesores de matemáticas.…”
Section: Tabla 1 Equivalencia Entre Las Dimensiones Que Componen El C...unclassified
“…85-86). Y también se ha estudiado en su relación con la orientación a la meta (Fernández, 2008), la vinculación con sus actitudes y creencias hacia el uso de las tecnologías de la comunicación (Letwinsky, 2017;OECD, 2019b), entre otras.…”
Section: Tabla 1 Equivalencia Entre Las Dimensiones Que Componen El C...unclassified